(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The effects of Neemark, commercial preparation obtained by neem (Azadirachta indica) seed kernels extract, on Tetranychus urticae Koch and Phytoseiulus persimilis Athias-Henriot were tested on bean leaf discs treated with different concentrations in laboratory experiments. Neemark can be considered moderately toxic for T. urticae but highly toxic for young stages and adults of Ph. persimilis at 3% and 5% concentrations. Also were investigated two new vegetable oils formulations 7094 and 1294 D/S on T. urticae in concentrations 0.5%, 1 % and 2% caused high toxicity and promise for the near future an alternative solution in the control of tetranychids in greenhouse culture and field crops.